Lower-body muscle structure and jump performance of stronger and weaker surfing athletes - Secomb, J. L.; Nimphius, S.; Farley, O. R. L.; Lundgren, L.; Tran, T. T.; Sheppard, J. M. (International Journal of Sports Physiology and Performance, 2016)
Purpose: